2023
DOI: 10.7150/thno.79367
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of dual immune checkpoint inhibitory signals with a CD47/PD-L1 bispecific antibody for cancer treatment

Abstract: Background: Even though PD-1/PD-L1 is an identified key "don't find me" signal to active adaptive immune system for cancer treatment, the overall response rate (ORR) for all cancer patients is still limited. Other effective therapeutic modalities to bridge the innate and adaptive immunity to improve ORR are urgently needed. Recently, CD47/SIRPα interaction is confirmed as a critical "don't eat me" signal to active innate immunity. However, the red blood cell (RBC) toxicity is the big concern for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Previous reports demonstrated lower binding of an affinity engineered anti-CD47 IgG4 antibody resulted in a better RBC toxicology profile (Thaker et al, 2022). Anti-PD-L1/anti-CD47 bispecific antibodies with significantly lower binding affinity of the anti-CD47 arm compared to the higher affinity anti-PD-L1 arm have been described (Chen et al, 2021;Wang et al, 2023) Such an approach has the potential to provide a better safety profile by preferentially targeting PD-L1/CD47 double positive tumors rather than single positive circulating RBC. QL401 has similar binding affinities and blocking capability for both anti-PD-L1 and anti-CD47 arms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports demonstrated lower binding of an affinity engineered anti-CD47 IgG4 antibody resulted in a better RBC toxicology profile (Thaker et al, 2022). Anti-PD-L1/anti-CD47 bispecific antibodies with significantly lower binding affinity of the anti-CD47 arm compared to the higher affinity anti-PD-L1 arm have been described (Chen et al, 2021;Wang et al, 2023) Such an approach has the potential to provide a better safety profile by preferentially targeting PD-L1/CD47 double positive tumors rather than single positive circulating RBC. QL401 has similar binding affinities and blocking capability for both anti-PD-L1 and anti-CD47 arms.…”
Section: Discussionmentioning
confidence: 98%
“…Because the rationale for combining blocking antibodies to PD-L1 and CD47 was compelling for both improving efficacy and safety, Frontiers in Drug Discovery frontiersin.org we, and others (Wang et al, 2020;Chen et al, 2021;Wang et al, 2023), have taken advantage of conventional antibody engineering to develop human anti-PD-L1/anti-CD47 therapeutic bispecific antibodies. Reported molecular structures vary, but have in common IgG1 or IgG4 backbones using knobs-in-holes technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on knobs-into-holes (KIH) platform, Wang et al . developed an anti-CD47 × PD-L1 BsAb 6MW3211, which was designed with a common light chain, exhibiting low affinity to CD47 and high affinity to PD-L1 [ 89 ]. This unique affinity profile allows preferential binding to PD-L1 of tumor cells, suppressing the CD47 signaling pathway [ 89 ].…”
Section: Anti-cd47 × Pd-l1 Bsabmentioning
confidence: 99%
“…Recent studies demonstrated that bispecific antibody or fusion protein against both PD‐L1 and CD47 showing better tumour‐cell targeting and stronger therapeutic effect than those of single blockade (Chen, Dominik, et al., 2021; Liu, Liu, et al., 2018). Thus, several studies on CD47/PD‐L1 bispecific antibody are in phase I/II clinical trials (Wang et al., 2023, 2020). However, dual targeting antibody and fusion protein had inherent limitations that curtailed their efficacy in this setting, including poor solid tumour penetration and affinity to ligands respectively (Dahan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%